A novel 17 bp InDel polymorphism within the PPARGC1A gene is significantly associated with growth traits in sheep. Issue 2 (1st April 2022) - Chen, Pingbo; Zhao, Haidong; Wu, Mingli; He, Shuai; Yuan, Tingting; Yi, Xiaohua; Liu, Shirong; Pan, Yun; Li, Qi; Wang, Shuhui; Sun, Xiuzhu
Abstract: Peroxisome proliferator-activated receptor gamma coactivator 1-alpha ( PPARGC1A ) is a member of transcriptional coactivator of the peroxisome proliferator-activated receptor. It is involved in lipid metabolism, energy metabolism, adipocyte differentiation and regulation of mitochondrial biogenesis. Therefore, the genetic variation of PPARGC1A gene will be of great value. The purposes of this study were to detect novel InDels within the PPARGC1A gene and analyze the effects of genetic polymorphisms on growth traits. We detected a novel 17 bp insertion polymorphism within the eleventh intron of the sheep PPARGC1A gene. Experimental results revealed that the InDel (insertion/deletion) genotypes distribution of the seven breeds of sheep was significant differences, of which three genotypes were detected. After correlation analysis, there were many significant phenotypic differences between the body size traits of the three genotypes. Interestingly, the dominant genotype was different in body weight both in STHS sheep and HS sheep. In summary, the 17 bp insertion polymorphism within the PPARGC1A gene had a great influence on the growth traits of sheep, which may provide a potential theoretical basis for marker-assisted selection in sheep genetic breeding.